Alternative Decompositions for Attributing Effects to Interactions. Issue 3 (May 2015) - VanderWeele, Tyler J.; Tchetgen Tchetgen, Eric J.
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.